A COMPARATIVE-TYPOLOGICAL STUDY OF LINGUOCULTURAL PHENOMENA IN UZBEK AND ENGLISH RIDDLES - Choriyeva Zebiniso Bakhtiyor qizi (Modern American Journals, 2025)
Tongue twisters represent a unique genre of oral folklore characterized by phonetic complexity, rhythmic repetition, and playful manipulation of language. This article presents a comparative analysis of the thematic organization and structural patterns of Uzbek and English tongue twisters from a linguistic and linguocultural perspective. The study aims to identify common and culture-specific features reflected in the thematic content and formal structure of tongue twisters in the two languages. The research employs comparative-typological, structural-semantic, and phonostylistic methods to analyze a representative corpus of Uzbek and English folk tongue twisters. The article contributes to folklore linguistics, comparative linguistics, and phonostylistics by offering a systematic classification and cross-linguistic interpretation of tongue twisters as a culturally embedded linguistic phenomenon.
Keywords: Tongue twisters, comparative linguistics, phonostylistics, Uzbek language, English language, folklore discourse, thematic organization, structural patterns